2017
DOI: 10.1007/s11096-017-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil citrate use in Addis Ababa: characteristics of users and pharmacists’ dispensing practices

Abstract: Background Studies have reported misuse of sildenafil citrate for recreational purpose, not least by healthy young men. This is becoming a major concern, for medical and other reasons. Objective The aim of this study was to document the characteristics of sildenafil citrate users and to explore the dispensing practices of the medicine in selected community pharmacies in Addis Ababa, Ethiopia. Setting Data was collected in community pharmacies in Addis Ababa, Ethiopia. Method A survey, using a self-administrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is essential to have medical consultation to treat ED as several medical risk factors could cause the disorder as stated previously. Overall, three-fourths of sexenhancing medication users consumed them after friends' consultations or via announcements, and only 19.9% of users had appropriate medical session [23] . According to a cross-sectional survey conducted in Egypt, 58.35% of sexenhancing medicine users obtained them for recreational purposes and 15.6% of them used drugs to improve the time and frequency of intercourse.…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to have medical consultation to treat ED as several medical risk factors could cause the disorder as stated previously. Overall, three-fourths of sexenhancing medication users consumed them after friends' consultations or via announcements, and only 19.9% of users had appropriate medical session [23] . According to a cross-sectional survey conducted in Egypt, 58.35% of sexenhancing medicine users obtained them for recreational purposes and 15.6% of them used drugs to improve the time and frequency of intercourse.…”
Section: Resultsmentioning
confidence: 99%
“…The nonprescription availability of sildenafil and other PDE5Is could lead to inappropriate use, increased adverse effects, and an increased probability of addiction among users. A study conducted in Addis Ababa, Ethiopia [19] on pharmacist dispensing practices of PDE5Is claimed that most pharmacists knew that PDE5Is are prescription-only medicines but still dispensed them without prescriptions. The motive for this practice was pressure to maximize profit through increased sales of PDE5Is.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ethiopian context, due to the lack of strong regulations, sildenafil can be easily accessed from pharmacies without a prescription (1,(9)(10)(11). A qualitative study conducted in Addis Ababa, Ethiopia revealed that there was a widespread use of sildenafil citrate and the main reasons for the utilization were to gain sexual confidence and suppress anxieties associated with a feeling of loss of manhood (12).…”
Section: Introductionmentioning
confidence: 99%